Analisis Semiotika Interaksi Sosial Narapidana Dalam Film 2037 Karya Mo Hong Jin - Mega Sari; Hamidah Hamidah; Jufrizal Jufrizal (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is motivated by dynamic social relationships, namely relationships between individuals, groups, or groups with groups, where these relationships have a reciprocal relationship. The movie 2037 was chosen because it has aspects of social interaction that occur in one environment, namely prisoners in a detention cell. This research aims to describe social interaction and also the forms of social interaction that occur in the movie 2037 directed by Mo Hong Jin. The results of this study found associative and dissociative forms of social interaction. The results are presented in the form of images, per-scene dialogue and gestures in each scene analyzed for denotation and connotation signs in the film 2037. Signs are displayed through several aspects such as the setting of the film, shooting techniques, scenes performed by character players and dialog between characters. These aspects then helped build the movie's storyline which resulted in a form of social interaction. Keywords: Film; Semiotics; Social Interaction;